2011
DOI: 10.1103/physrevlett.107.043603
|View full text |Cite
|
Sign up to set email alerts
|

Collective Dynamics in Optomechanical Arrays

Abstract: Optomechanical systems couple light stored inside an optical cavity to the motion of a mechanical mode. Recent experiments have demonstrated setups, such as photonic crystal structures, that in principle allow one to confine several optical and vibrational modes on a single chip. Here we start to investigate the collective nonlinear dynamics in arrays of coupled optomechanical cells. We show that such "optomechanical arrays" can display synchronization, and that they can be described by an effective Kuramoto-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
394
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 398 publications
(404 citation statements)
references
References 36 publications
6
394
0
4
Order By: Relevance
“…Unlike our model, the mechanical resonators in Heinrich et al interact with a local electromagnetic field mode and are directly coupled by elastic forces. The more complex coupling in our model results in a different mechanism for the loss of synchronisation which typically occurs for large amplitude forcing not small amplitude forcing as occurs in the model of Heinrich et al [10]. Nevertheless we are able to give specific results on synchronisation for two and three mechanical resonators interacting via a common cavity mode and relate these to the behaviour of a collective variable, which is related to the cavity field amplitude.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Unlike our model, the mechanical resonators in Heinrich et al interact with a local electromagnetic field mode and are directly coupled by elastic forces. The more complex coupling in our model results in a different mechanism for the loss of synchronisation which typically occurs for large amplitude forcing not small amplitude forcing as occurs in the model of Heinrich et al [10]. Nevertheless we are able to give specific results on synchronisation for two and three mechanical resonators interacting via a common cavity mode and relate these to the behaviour of a collective variable, which is related to the cavity field amplitude.…”
Section: Introductionmentioning
confidence: 61%
“…This multi stable behaviour, resulting from the play off between weak damping and cavity forcing, has been noted elsewhere [8,10,24]. Here we explore it in more depth using amplitude equations.…”
Section: B Amplitude Equations and Multi-stability For Blue Detuningmentioning
confidence: 99%
See 2 more Smart Citations
“…Several experimental works have shown that synchronization can be observed in the laboratory within Josepshon junction arrays [40], nanomechanical systems [17], or optomechanical systems [41]. All of these systems share one prominent property: They behave quantum mechanically at sufficiently low temperatures.…”
Section: Discussionmentioning
confidence: 99%